DESIGN, PERFORMANCE ANALYSIS AND EFFICIENCY OPTIMIZATION OF COPPER INDIUM GALLIUM SELENIDE (CIGS) SOLAR CELL - Shamim, S M; Islam, Shariful; Huq, Md Fazlul; Al Jobair, Md.Abdullah (European Scientific Journal, ESJ, 2015)
A comparative investigation of the cell performance of Copper Indium Gallium Selenide (CIGS) thin-film solar cell, fabricated using ZnO:Al/i-ZnO/CdS/CIGS layers, has been reported. ADEPT 2.0, a 1D simulation software, were used throughout the whole research for the simulation of light J-V characteristics for different designs. Energy conversion efficiency for each design was calculated from its corresponding light J-V characteristics curve. The efficiency variation were investigated under 1 sun, AM1.5G illumination and optimized layer parameters (thickness) for each layer of the device. The device has designed with an ntype ZnO window layer, an n-type CdS as buffer layer and a p-type CIGS as absorber layer. Molybdenum (Mo) substrate is used for the structure. A totalarea efficiency of 19·75% for ZnO:Al/i-ZnO/CdS/CIGS based thin-film solar cells had been found. Performance is improved due to higher fill factor. The device parameters are optimized separately for each layer. Based on these optimizations, the ultra-thin film solar cell design is proposed after careful consideration of lattice mismatch between two adjacent layers of the device.